Tinea Faciei Successfully Treated with Individualised Homoeopathic Medicine: A Case Report - Ram, Hanuman; Singh, Uttam (Homœopathic Links, 2023)
Tinea faciei (TF) is a clinical form of superficial dermatophyte infection that is frequently misdiagnosed due to its variable appearance on the smooth regions of the face and affects both sexes and all age groups. Treatment in the conventional system of medicine uses local and systematic antifungals. Homoeopathic materia medica and repertory have highlighted beneficial medicines for TF. Here, we report one case of a 22-year-old female patient complaining of multiple erythematous, circumscribed lesions with elevated margins and mild scaling on the right side of the face and upper neck region. There was marked itching and burning in the lesions. The patient was diagnosed with TF (ringworm of the face). Sepia officinalis was prescribed after a detailed case taking, repertorisation and final consultation with materia medica based on the totality of symptoms. Within 3 months of administration of individualised homoeopathic medicine Sepia officinalis, multiple erythematous, circumscribed lesions with elevated margins and scaling completely disappeared. During another 6 months of subsequent follow-ups, no symptoms were observed. The present case report addresses the importance of individualised homoeopathic approach in TF infections. The improvement in the case was assessed clinically by a pre-determined 4-point scale and through photographic evidence at baseline, during and after treatment. The modified Naranjo criteria score after treatment was seven (7), establishing a positive causal attribution of the individualised homoeopathic medicine Sepia officinalis for this case. Homoeopathic treatment adhering to its ground principles of individualisation has shown promising and favourable results in this case.
Keywords: tinea faciei; individualised homoeopathy; modified Naranjo criteria; Sepia officinalis